The perceptions of the causes of cardiac diseases: a taxonomy. Issue 4 (3rd April 2018) - Miglioretti, Massimo; Meroni, Claudia; Baiardo, Giacomo; Savioli, Gaia; Velasco, Veronica
Abstract : Objective: This study verifies whether the open-ended question of the B-IPQ can collect causal attributions of patients with cardiac diseases, define the more frequent causal attributions reported, classify them and describe the relation between the classification of the causes and patients' characteristics. Design: A group of 2011 patients with cardiac diseases was recruited during the first week of cardiac rehabilitation. Primary outcome measures: Every participant filled in the B-IPQ and the HADS. The qualitative and quantitative analyses of the text using T-LAB identified the most frequent causal attributions and their co-occurrences. Results: Among the patients, 26% did not recognise any causal attribution. The likelihood that the patients did not provide an answer was increased in older patients, females, patients with lower levels of education and higher levels of depression. Smoking and stress emerged as the most important attributions, followed by genetics, metabolic syndrome, work and nutrition. Four thematic clusters were identified: 'work and stress', 'metabolic syndrome and hypertension', 'displeasures and body care' and 'heredity and other related diseases'. Conclusions: This study suggests a classification of the causal attributions in patients with cardiac diseases and identifies thematic patterns and unknown attributions. The themes identified can serve as categories for future closed-ended questions.